The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/sd.2227
|View full text |Cite
|
Sign up to set email alerts
|

Challenges facing indicators to become a universal language for sustainable urban development

Abstract: Urban development plays a role in global progress, but its sustainability is still a pressing issue. Indicators are a kind of powerful tool for addressing issues about urban sustainability and have gained increasing attention. However, making them become a universal "language" to solve this global issue is still challenging and controversial. This paper firstly summarizes 1442 indicators in the previous 47 urban sustainability studies. Then, based on the discussion of deficiencies in framing, conceptualizing, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…The concept of sustainability is growing in importance for local urban governance, and indicator-based assessments represent a popular means for its implementation [81]. Indicators are a powerful tool to address urban sustainability issues and have gained increasing attention [82]. However, making them a universal 'language' to solve this global problem remains a challenge and a controversy.…”
Section: Global Numerical Resultsmentioning
confidence: 99%
“…The concept of sustainability is growing in importance for local urban governance, and indicator-based assessments represent a popular means for its implementation [81]. Indicators are a powerful tool to address urban sustainability issues and have gained increasing attention [82]. However, making them a universal 'language' to solve this global problem remains a challenge and a controversy.…”
Section: Global Numerical Resultsmentioning
confidence: 99%
“…Firstly, the indicator system of the urban system is established in consideration of data accessibility and previous studies [35,36,40,41], as shown in Table 2. This paper mainly collects data from Shanghai Statistical Yearbooks, and the simulation span is 1995-2030.…”
Section: Indicator System and Data Sourcementioning
confidence: 99%
“…Indicators are things that we measure for different purposes like comparing cases, exploring relationships between variables, and raising public awareness (Miller, 2001). Meanwhile, Ruan and Yan (2022, 41) define indicators as “measurable and quantifiable variables that are the building blocks of any objective assessment”. In other words, a main utility of indicators is to show how far we are from our objectives and identify problem areas (Dizdaroglu, 2015).…”
Section: Introductionmentioning
confidence: 99%